Victims of Road Traffic Accidents in Ethiopia Their Experiences and Coping Strategies - Betelihem Getachew; Zena Berhanu Sisay; Messay Gebremariam Kotecho (Ethiopian Journal of the Social Sciences and Humanities)
The rising incidence of physical injuries from road traffic accidents in developing countries significantly impacts individuals' psychological well-being and social connections. Most existing studies, which are predominantly quantitative, focus on accident causes and prevention methods; they often overlook the lived experiences of victims. This qualitative phenomenological study aimed to delve into the often overlooked experiences and coping strategies of individuals with physical injuries resulting from road accidents, using in-depth interviews with ten participants. Thematic analysis revealed that while support was available from various sources, it was often incomplete and delayed. Additionally, uninformed medical decisions were common, with individuals receiving little explanation about their condition or future treatment. Hospitalization was generally viewed negatively, and coping strategies included support from loved ones and resilience drawn from personal experiences developed during the recovery process. Recognizing these sources of support is crucial for facilitating adaptation and improving overall quality of life. The study highlights the vital role of the social work profession in offering emotional and psychosocial support and improving communication between patients and the medical team to address mental health challenges.